2019
DOI: 10.1002/hyp.13587
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic traits that buffer deep‐rooted plants from changes in hydrology and climate

Abstract: Groundwater‐dependent ecosystems are often defined by the presence of deeply rooted phreatophytic plants. When connected to groundwater, phreatophytes in arid regions decouple ecosystem net primary productivity from precipitation, underscoring a disproportionately high biodiversity and exchange of resources relative to surrounding areas. However, groundwater‐dependent ecosystems are widely threatened due to the effects of water diversions, groundwater abstraction, and higher frequencies of episodic drought and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 92 publications
(152 reference statements)
8
72
0
Order By: Relevance
“…Significant differences were observed in most pairs of comparisons within both measured populations (Table 3). cooler temperatures illustrated greater transpiration rate (Hultine et al, 2020a) and presumably higher water content. Linking ground-based leaf and canopy temperature measurements with UAV-based thermal estimates need further testing and development in various climates and environments.…”
Section: Uav Thermal Remote Sensingmentioning
confidence: 98%
See 1 more Smart Citation
“…Significant differences were observed in most pairs of comparisons within both measured populations (Table 3). cooler temperatures illustrated greater transpiration rate (Hultine et al, 2020a) and presumably higher water content. Linking ground-based leaf and canopy temperature measurements with UAV-based thermal estimates need further testing and development in various climates and environments.…”
Section: Uav Thermal Remote Sensingmentioning
confidence: 98%
“…We completed the ground-based leaf temperature measurements in the common garden on May 30, 2019 at midday between 12:00 and 14:00 h. We measured leaf temperatures of 60 individual trees that represented two populations and 10 genotypes: five genotypes of the hot SD population from the local Agua Fria National Monument (Population #8, Table 1) and five genotypes of the cool HP population from Keams Canyon (Population #16, Table 1). These populations and genotypes were selected to represent Fremont cottonwood trees adapted to the very hot and cool origins of the broad environmental gradient sampled for the common garden and based on our previous ground-based results (Hultine et al, 2020a). Each population was sampled from two different blocks and two different plots.…”
Section: Ground-based Measurementsmentioning
confidence: 99%
“…A recent common garden experiment conducted at the mid-elevation common garden ( Fig. 3 ) revealed that chronic exposure to intense heat waves could impose strong selection pressures on P. fremontii to maximize canopy thermal regulation via a suite of hydraulic strategies ( Hultine et al ., 2020 ). Genotypes sourced from the extremely warm SD ecoregion had midday leaf temperatures in midsummer that were on average 2.0°C (SE ± 0.58) below ambient temperature; while genotypes sourced from the higher elevation, cooler UHP ecoregion had leaf temperatures that were on average 2.1°C (SE ± 0.67) above ambient temperature ( Fig.…”
Section: Trade-offs Between Thermal Regulation and Hydraulic Riskmentioning
confidence: 99%
“…4a ). The cooler leaf temperatures corresponded with the warm-adapted, SD ecotypes having a 35% higher midday leaf transpiration rate ( E ) relative to the UHP ecotypes, resulting in substantially greater leaf evaporative cooling ( Hultine et al ., 2020 ). Although predawn leaf water potentials (Ψ pd ) were similar between the two ecotypes, minimum leaf water potentials (Ψ min ) during midday were on average 0.2 MPa lower in the SD ecotypes ( Fig.…”
Section: Trade-offs Between Thermal Regulation and Hydraulic Riskmentioning
confidence: 99%
“…In previous reports, obligate riparian species, such as cottonwoods, show they are restricted to places with specific groundwater levels [30,65]. On the other hand, mesquite and other facultative riparian species are distributed near streams with varying levels, but are usually found where groundwater is at deeper levels than those required for the establishment or sustenance of obligate riparian species [66,67]. Thus, the spatial differentiation between obligate riparian and facultative riparian species is crucial, since the absence of obligate riparian species could serve as an indicator of a decline in water availability [68].…”
Section: Riparian Vegetation and Agriculturementioning
confidence: 99%